The effect of training order on neuromuscular, endocrine and mood response to small-sided games and resistance training sessions over a 24-h period - Sparkes, W.; Turner, A. N.; Weston, M.; Russell, M.; Johnston, M. J.; Kilduff, L. P. (Journal of Science and Medicine in Sport, 2020)
Objectives: This study examined the acute effect of small-sided-game (SSG) and resistance training sequence on neuromuscular, endocrine and mood response over a 24-h (h) period. Design: Repeated measures. Methods: Fourteen semi-professional soccer players performed SSG-training (4vs4+goalkeepers; 6×7-min, 2-min inter-set recovery) followed by resistance training 2h later (back-squat, Romanian deadlift, barbell-hip-thrust; 4×4 repetitions, 4-min inter-set recovery; 85% 1 rep-max) (SSG+RES), and on a separate week reversed the session order (RES+SSG). Physical demands of SSG`s were monitored using global positioning systems (GPS) and ratings of perceived exertion (RPE). Countermovement-jump (CMJ; peak power output; jump height) and brief assessment of mood were collected before (pre), during (0h) and after (+24h) both protocols. Salivary testosterone and cortisol concentrations were obtained at the same time-points but with the inclusion of a measure immediately prior to the second training session (+2h). Results: GPS outputs and RPE were similar between SSG-training during both protocols. Between-protocol comparisons revealed no significant differences at +24h in CMJ performance, mood, and endocrine markers. Testosterone was higher at 0h during RES+SSG in comparison to SSG+RES (moderate-effect; +21.4±26.7pgml-1; p=0.010), yet was similar between protocols by +2h. Conclusions: The order of SSG and resistance training does not appear to influence the physical demands of SSG`s with sufficient recovery between two sessions performed on the same day. Session order did not influence neuromuscular, endocrine or mood responses at +24h, however a favourable testosterone response from the resistance first session may enhance neuromuscular performance in the second session of the day.